Educational training programs on intimate partner violence in pregnancy for midwives/student midwives: A scoping review - Manoli, Emmanouela; Kouta, Christiana; Karanikola, Maria; Middleton, Nicos; Hadjigeorgiou, Eleni (My University, 2024)
Educational strategies for preventive screening and effective interventions in midwives are needed to improve clinical practice and outcomes for abused women and their families. This scoping review aimed to describe available educational training programs on intimate partner violence (IPV) in pregnancy for midwives/student midwives.
Keywords: student midwife; educational training; evaluation; intimate partner violence; midwives; pregnancy